2010
DOI: 10.1002/ajim.20805
|View full text |Cite
|
Sign up to set email alerts
|

Informal social status among coworkers and risk of work‐related injury among nurse aides in long‐term care

Abstract: Findings of this exploratory study were internally consistent and support a theoretical framework suggesting that patterns of social relations between individuals based on informal social status in the workplace may contribute to differences in work-related injury risk among individuals with the same job title.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…A previous review noted that hesitancy to express concerns can be a key contributing factor to communication errors [32]. Another previous study revealed that nurse aides with a higher informal social status had greater access to help from co-workers and reduced exposure to possible injury risk [33].…”
Section: Discussionmentioning
confidence: 99%
“…A previous review noted that hesitancy to express concerns can be a key contributing factor to communication errors [32]. Another previous study revealed that nurse aides with a higher informal social status had greater access to help from co-workers and reduced exposure to possible injury risk [33].…”
Section: Discussionmentioning
confidence: 99%
“…Such situations have also been concluded by the multi-group analysis of the following structural equation model. For a deeper consideration of such phenomenon, female employees have always been supposed to possess higher levels of work-family conflict (less social support), more physical/mental demands (higher job demands) compared to male employees [43, 44]; younger workers are often supposed to have less experiences/skills (low job control), more monotonous ground work (higher demand), and less job reward [45]; and compared to technicians and physicians, nurses have more opportunity to access sharp instruments, and their heavy work load also relates to higher job demands and effort [46, 47]. In other words, these demographic characteristics, which often go alone with risking psychosocial working conditions are more susceptible to working injury under the circumstance of occupational stress [47].…”
Section: Discussionmentioning
confidence: 99%
“…In their review study [ 12 ], McCaughey et al also showed that having peer support [ 14 ] and collaboration among colleagues [ 15 ] decreased the risk of injury among nurses, and that nurses’ aides with higher informal social status had greater access to help from co-workers and reduced exposure to injury risk [ 14 ]. The authors inferred from these findings that social-relational aspects of work such as informal social status, a supportive culture, and social support may have an effect on injury risk among employees [ 12 ].…”
Section: Introductionmentioning
confidence: 99%